Issues of Legal Organization of the Patient-Health Care Professional Relationship - Kudeikina, Inga; Mg.iur. Karina Palkova (European Journal of Multidisciplinary Studies, 2016)
Nowadays increasing attention is paid to the issues of legal organization of the patient-health care professional relationship. One of the issues in this field is the institution of the rights and obligations of the patients and the medical practitioners. Cases when the doctor restricts the rights of the patient while fulfilling his duties or vice versa are rare. Interaction of the scope of rights and obligations of the patients and medical practitioners causes complicated situation. The author believes that solution to such situation is to be found in the human rights standards. The article discusses the issue regarding the grounds, on which the legal relationship of the patient and the health care professional are created, and how they are organized. The issues of the patient-health care professional relationship are viewed from the perspective of the human rights. Rights to life and health form the fundamental principle of the human rights, which is integrated in the national and international legal acts. The aim of the article is to provide insight to the role played by fundamental principle of the human rights, principles in the relationship of the patients and medical practitioners. Analyses show that human rights in relations between patients and health care professionals are absolute.